Radiotherapy treatment volumes for oligorecurrent nodal prostate cancer: a systematic review. (2nd October 2020) - Achard, Verane; Bottero, Marta; Rouzaud, Michel; Lancia, Andrea; Scorsetti, Marta; Filippi, Andrea Riccardo; Franzese, Ciro; Jereczek-Fossa, Barbara Alicja; Ingrosso, Gianluca; Ost, Piet; Zilli, Thomas
Abstract: Background: Radiotherapy is an emerging treatment strategy for nodal oligorecurrent prostate cancer (PCa) patients. However, large heterogeneities exist in the RT regimens used, with series reporting the use of elective nodal radiotherapy (ENRT) strategies and others the delivery of focal treatments to the relapsing nodes with Stereotactic Body Radiotherapy (SBRT). In this systematic review of the literature we compared the oncological outcomes and toxicity of the different RT regimens for nodal oligorecurrent PCa patients, with the aim of defining the optimal RT target volume in this setting. Methods: We performed a systemic search on the Pubmed database to identify articles reporting on the use of ENRT or SBRT for oligometastatic PCa with nodal recurrence. Results: Twenty-two articles were analyzed, including four prospective phase II trials (3 with SBRT and 1 with ENRT). Focal SBRT, delivered with an involved node, involved site, and involved field modality, was the most commonly used strategy with 2-year progression-free survival (PFS) rates ranging from 16 to 58% and a very low toxicity profile. Improved PFS rates were observed with ENRT strategies (52–80% at 3 years) compared to focal SBRT, despite a slightly higher toxicity rate. One ongoing randomized phase II trial is comparing both modalities in patients with nodal oligorecurrent PCa. Conclusions: With a large variability in patterns of practice, the optimal RT strategy remains to be determined in the setting of nodal oligorecurrent PCa. Ongoing randomized trials and advances in translational research will help to shed light on the best management for these patients. .